Optimal scoring of serial change on chest radiography in sarcoidosis - Zappala, C.J.; Desai, S.R.; Copley, et al., S.J. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2011)
Background: The optimal means of quantifying change on chest radiography in sarcoidosis is uncertain. In current guidelines, the role of serial measurement of carbon-monoxide diffusing capacity (DLCO) remains undefined and the prevalence of discordance between serial chest radiographic change and pulmonary function tends is unknown. Objective: To identify and explore key uncertainties in the monitoring of sarcoidosis by serial pulmonary function tests and chest radiography. Design: 354 patients with sarcoidosis and concurrent tests (chest radiography and PFTs within three months at baseline, two years and/or four years) were studied. Chest radiographs were assessed by two radiologists for changes in stage and disease extent. Radiographic change and pulmonary function trends were quantified and compared. Results: Change in radiographic extent of lung disease was always more frequent than change in stage (p